The Feasibility of Rice Seed Capture Business - Irvan Syah, Muhamad; Widyantari, Ineke Nursih; Ginting, Nina Maksimiliana (Universitas Djuanda, 2024)
The study aimed to determine the income of rice seed breeding farmers and the feasibility of the rice seed breeding business. The research site was selected purposely, considering Semangga District is a rice-producing area in Merauke Regency. The study population amounted to 32 farmers who were sampled, so the sampling method was a census. This research uses primary data obtained through surveys, interviews, and questionnaires, and secondary data obtained through the internet, journals, and other literature. The results obtained were farmer income of Rp. 22,754,654. The R / C Ratio value of 2.12, because it is greater than one, then the rice seed breeding business in the study area is feasible to develop.